Marble-hosted ruby deposits of the Morogoro Region, Tanzania. (October 2017) - Balmer, Walter A.; Hauzenberger, Christoph A.; Fritz, Harald; Sutthirat, Chakkaphan
Abstract: The ruby deposits of the Uluguru and Mahenge Mts, Morogoro Region, are related to marbles which represent the cover sequence of the Eastern Granulites in Tanzania. In both localities the cover sequences define a tectonic unit which is present as a nappe structure thrusted onto the gneissic basement in a north-western direction. Based on structural geological observations the ruby deposits are bound to mica-rich boudins in fold hinges where fluids interacted with the marble-host rock in zones of higher permeability. Petrographic observations revealed that the Uluguru Mts deposits occur within calcite-dominated marbles whereas deposits in the Mahenge Mts are found in dolomite-dominated marbles. The mineral assemblage describing the marble-hosted ruby deposit in the Uluguru Mts is characterised by corundum-dolomite-phlogopite ± spinel, calcite, pargasite, scapolite, plagioclase, margarite, chlorite, tourmaline whereas the assemblage corundum-calcite-plagioclase-phlogopite ± dolomite, pargasite, sapphirine, titanite, tourmaline is present in samples from the Mahenge Mts. Although slightly different in mineral assemblage it was possible to draw a similar ruby formation history for both localities. Two ruby forming events were distinguished by textural differences, which could also be modeled by thermodynamic T–XCO2 calculations using non-ideal mixing models of essential minerals. A first formation of ruby appears to have taken place during the prograde path (M1) either by the breakdown of diaspore which was present in the original sedimentary precursor rock or by the breakdown of margarite to corundum and plagioclase. The conditions for M1 metamorphism was estimated at ∼750 °C at 10 kbar, which represents granulite facies conditions. A change in fluid composition towards a CO2 dominated fluid triggered a second ruby generation to form. Subsequently, the examined units underwent a late greenschist facies overprint. In the framework of the East African Orogen we assume that the prograde ruby formation occurred at the commonly observed metamorphic event around 620 Ma. At the peak or during beginning of retrogression the fluid composition changed triggering a second ruby generation. The late stage greenschist facies overprint could have occurred at the waning stage of this metamorphic episode which is in the range of ∼580 Ma. Graphical abstract: Highlights: Two marble-hosted ruby deposits in the meta -carbonate cover sequence of the Eastern Granulites, Tanzania are examined. Two tectono-metamorphic events could be linked to the EAO between ∼610 and 580Ma. Thermodynamic T-XCO2 calculations indicate Granulite Facies conditions for M1 peak metamorphism at ∼750 °C and 10 kbar. Structural and petrographic studies revealed a structurally controlled deposit style. Fluid-rock interaction related to mine-scale fold structures created a saddle reef deposit.